Drivers of working hours and household income dynamics during the COVID-19 pandemic: The case of the Netherlands - Christian Zimpelmann; Hans-Martin vonGaudecker; Radost Holler; Lena Janys; Bettina Siflinger (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Using customized panel data spanning the entire year of 2020, we analyze the dynamics of working hours and household income across different stages of the CoVid-19 pandemic. Similar to many other countries, during this period the Netherlands experienced a quick spread of the SARS-CoV-2 virus, adopted a set of fairly strict social distancing measures, gradually reopened, and imposed another lockdown to contain the second wave. We show that socio-economic status is strongly related to changes in working hours, especially when strict economic restrictions are in place. In contrast, household income is equally unaffected for all socio-economic groups. Examining the drivers of these observations, we find that pandemic-specific job characteristics (the ability to work from home and essential worker status) explain most of the socio-economic gradient in total working hours. Furthermore, household income is largely decoupled from shocks to working hours for employees. We provide suggestive evidence that large-scale labor hoarding schemes have helped insure employees against demand shocks to their employees.
Keywords: D31; J21; J22; J24; J33; 330; inequality; labor market; working from home; coronavirus; essential workers; mitigation policies